MR imaging and spectroscopy in degenerative ataxias: toward multimodal, multisite, multistage monitoring of neurodegeneration. Issue 4 (August 2020) - Öz, Gülin; Harding, Ian H.; Krahe, Janna; Reetz, Kathrin
Abstract : Purpose of review: Degenerative ataxias are rare and currently untreatable movement disorders, primarily characterized by neurodegeneration in the cerebellum and brainstem. We highlight MRI studies with the most potential for utility in pending ataxia trials and underscore advances in disease characterization and diagnostics in the field. Recent findings: With availability of advanced MRI acquisition methods and specialized software dedicated to the analysis of MRI of the cerebellum, patterns of cerebellar atrophy in different degenerative ataxias are increasingly well defined. The field further embraced rigorous multimodal investigations to study network-level microstructural and functional brain changes and their neurochemical correlates. MRI and magnetic resonance spectroscopy were shown to be more sensitive to disease progression than clinical scales and to detect abnormalities in premanifest mutation carriers. Summary: Magnetic resonance techniques are increasingly well placed for characterizing the expression and progression of degenerative ataxias. The most impactful work has arguably come through multi-institutional studies that monitor relatively large cohorts, multimodal investigations that assess the sensitivity of different measures and their interrelationships, and novel imaging approaches that are targeted to known pathophysiology (e.g., iron and spinal imaging in Friedreich ataxia). These multimodal, multi-institutional studies are paving the way to clinical trial readiness and enhanced understanding of disease in degenerative ataxias.